Ranking socioeconómico para el desarrollo de las regiones carboníferas en Europa - Sergio A. Berumen; Luis P. Pérez-Megino (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
– The socioeconomic situation of European coalfields is highly heterogeneous. On the one hand, successful examples comprise regions that long ago embraced internationalization, innovation and/or restructuring strategies. In those regions where the aforementioned strategies were fruitful, the development of new production methods led to gradual repopulation. Less successful examples, however, are likely to experience undesired effects as a consequence of both the suppression of aid (EU- and regional- level) and the liberalization of EU mining markets, starting on December 31, 2018. This papers aims to provide a method to accurately assess the socioeconomic situation of these egions. As such a method is rooted in previous policies, it enables the identification of welfare-enhancing policies for the inhabitants of European coalfield regions.
Keywords: C38; L16; L72; O57; R11; 330; economic development; coalfield regions and municipalities; mining sector; coal-mining companies; quantitative methods